LC-MS/MS Based Quantitative Analysis of Remogliflozin in Rat Plasma: A Kinetic Study Approach - Patel, Smit J.; Mehta, Hiralben; Shaikh, Basheer; Khan, Nadeem (Journal of Neonatal Surgery, 2025)
This research utilized high-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method to quantitatively measure concentration of remogliflozin in rat plasma using bixafen as the internal standard. Samples were prepared by aqueous acetonitrile-based protein precipitation technique. Remogliflozin was then analysed by isocratic elution chromatography with a mobile phase consisting of 0.1% formic acid in milli-Q water (20): acetonitrile (80). Remogliflozin was monitored by m/z 451.4→289.4 transition for quantification and m/z 451.4→111.2 transition for qualification, and bixafen was determined by m/z 414.0→ 394 by multiple reaction monitoring (MRM) in positive ion electrospray ionization (ESI) source. Method exhibited good linearity in the range of 15 ng/mL to 2009 ng/mL. During pharmacokinetic experiments involving oral administration of remogliflozin in rat, the time to reach maximum concentration (Tmax) was found to 0.5 h in both males and females. The maximum concentration (Cmax) was found to be 201 ng/mL in males and 293 ng/mL in females while the last area under the concentration-time curve (AUClast) was determined to be 448 ng*h/mL for males and 297 ng*h/mL for females.